Substitution of calcium with neodymium and dysprosium in hydroxyapatite structure - Get‘man, E.I.; Loboda, S.N.; Tkachenko, T.V.; Ignatov, A.V.; Zabirko, T.F. (Functional Materials, 2005)
Using X-ray phase analysis, the calcium substitution with Nd and Dy in hydroxyapatite Са₁₀₋xLnx(РО₄)₆(ОН)₂-хОх at 1100°C has been established to take place up to x = 2.0 and 1.4, respectively. The IR spectroscopy has shown that along with the Ca²⁺ +ОH⁻ → Ln⁺³ + O²⁻ substitution, the 2ОH⁻ O²⁻ + □ one occurs. The structure refinement using Rietveld method has shown that Nd and Dy ions occupy mainly the Ca(2) positions. The Ca²⁺ + ОH⁻ → Ln3⁺ + O²⁻ substitution has been established to strengthening of the Ca(2)-O(4) bond but weakens somewhat the Ca(2)-O(1,2,3) ones.